Examining Oral Reading Fluency Trajectories Among English Language Learners and English Speaking Students - Shane R. Jimerson; Sehee Hong; Scott Stage; Michael Gerber (Springer, 2013)
Students' oral reading fluency growth from first through fourth grade was used to predict their achievement on the Stanford Achievement Test (9th ed.; SAT-9 Reading) using a latent growth model. Two conditional variables related to student status were used to determine the effects on reading performance - English language learners (ELLs) with low socioeconomic status and low socioeconomic (SES) status alone. Results revealed that both types of student status variables reliably predicted low performance on initial first grade oral reading fluency, which later predicted fourth grade performance on the SAT-9. However, the reading fluency trajectories of the ELLs and monolingual English students were not significantly different. In addition, when both student status variables and letter naming fluency were used to predict initial oral reading fluency, letter naming fluency dominated the prediction equation, suggesting that an initial pre-reading skill, letter naming fluency, better explained fourth grade performance on the SAT-9 than either ELL with low SES or low SES alone. The discussion focuses on how to better enable these readers and how oral reading fluency progress monitoring can be used to assist school personnel in determining which students need additional instructional assistance.